Предмет: Алгебра, автор: sagsgasgga

СРОЧНО РЕШИТЕ! ДАЮ 35 БАЛЛОВ!

Приложения:

Ответы

Автор ответа: nikebod313
3

\displaystyle \left({\frac{a+ x}{x}}^{\setminus \cdot (x-a)} - {\frac{2x}{x - a}}^{\setminus  \cdot x} \right) \cdot \frac{x - a}{a^{2} + x^{2}} = \frac{(a + x)(x - a) - 2x^{2}}{x(x - a)} \cdot \frac{x - a}{a^{2} + x^{2}} =\\= \frac{x^{2} - a^{2} - 2x^{2}}{x} \cdot \frac{1}{a^{2} + x^{2}} = \frac{-(a^{2} + x^{2})}{x(a^{2} + x^{2})} = -\frac{1}{x}

Похожие вопросы
Предмет: Алгебра, автор: vovashapovalov2